The Influence of Transparency and Accountability on the Financial Management of Village-Owned Enterprises (BUMDes) in Suralaga Subdistric - Lestari, Tika Fuji; Sulkiah, Sulkiah (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to analyze the influence of transparency and accountability on the financial management of Village-Owned Enterprises (BUMDes) in the Suralaga Sub-District. This means that the researcher seeks to determine the extent to which transparency and accountability affect the quality of financial management carried out by BUMDes administrators.The research method used is quantitative, which refers to an approach that emphasizes objective measurement of social phenomena through numerical data and statistical analysis.The data collection technique used in this study is a questionnaire, which serves to obtain primary data from respondents, namely BUMDes managers in the Suralaga Sub-District. The collected data were analyzed using multiple linear regression and Partial Least Squares-Structural Equation Modeling (PLS-SEM) through the SmartPLS software.The results of this study indicate that transparency does not affect the financial management of BUMDes in Suralaga District unless it is accompanied by adequate access and human resource capacity. In contrast, accountability has a significant effect on the financial management of BUMDes in the same area. Good accountability ensures that every use of funds, assets, and activities is properly reported and can be accounted for to both the public and the government.Transparency is defined as public access to data or information, along with clarity regarding government rules and services. Accountability refers to the obligation to report and be answerable for an institution’s achievements or failures in fulfilling its predetermined vision and goals